ANALISIS KEPUASAN PASIEN RSUD PONDOK AREN TERHADAP LAYANAN BPJS RAWAT JALAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Cendrawasih; Reva Nugraha Fadhillah; Kiki Rieswanto; Sulistiyah; Adhy Purnawan (Universitas Majalengka, 2025)
RSUD Pondok Aren faces challenges in outpatient services as the number of BPJS participants continues to grow, particularly regarding waiting time and perceived service quality. This study aims to evaluate patient satisfaction with BPJS outpatient services using the Analytical Hierarchy Process (AHP). Five key criteria were assessed: registration waiting time, examination waiting time, medication pickup time, service quality, and facility availability. Data were collected from 36 respondents, comprising medical/non-medical staff and both BPJS and non-BPJS patients. The analysis identified service quality as the most dominant criterion (weight: 0.341), followed by facility availability (0.222). The priority synthesis revealed that non-BPJS patients had a higher satisfaction score (0.69392) than BPJS patients (0.30598), indicating a service perception gap. A consistency ratio (CR) of 0.034 confirms the logical validity of respondent judgments. This study provides strategic recommendations to improve BPJS outpatient service quality based on multistakeholder preferences.